Applied predictive thermodynamics (ThermAP). Part 2. Apatites containing Ni2+, Co2+, Mn2+, or Fe2+ ions. (September 2019) - Drouet, Christophe
Graphical abstract: Highlights: The ThermAP additive model was enlarged to divalent metal ions in phosphate apatite. Thermodynamic properties of Ni-, Co-, Mn(II)- and Fe(II)-apatites were estimated. Evaluated stability ranking Mn(II)-apatite > Fe(II)-apatite > Co-apatite ⩾ Ni-apatite. This predictive model was also applied to solid solutions. Data may be useful in domains of geochemistry, bone diagenesis, water treatment. Abstract: Apatites are minerals encountered in many fields including geochemistry, nuclear and environmental sciences as well as medicine. This ubiquity is likely related to the diversity of ion substitutions that the apatite structure can accommodate, making of it an excellent "ion reservoir" either in natural settings or for the intentional production of doped systems with tailored properties. Despite this widespread interest for apatite compounds, however, only few studies are dedicated to study their thermodynamic properties. Yet, their knowledge becomes necessary for assessing stability domains and understanding evolutionary trends in solution or upon heating, for example. Recently, the experimental thermodynamics of 33 phosphate apatite compounds (deriving from the composition M10 (PO4 )6 X2 ) have been reviewed and their comparison allowed the development of the additive predictive model " ThermAP " ( Applied Predictive Thermodynamics ) capable of adequately predicting properties such as standard enthalpies ( Δ H f ∘ ), Gibbs free energies of formation ( Δ G f ∘ ), or entropies (S°) at T = 298 K, for any composition involving ions among M 2+ = Ca 2+, Ba 2+, Sr 2+, Mg 2+, Cd 2+, Pb 2+, Cu 2+, Zn 2+ and X − = OH −, F −, Cl − or Br − . Although experimental data for apatites involving other divalent cations such as Ni 2+, Co 2+, Mn 2+ or Fe 2+ do not seem to be available, the exploration of apatites doped with these ions is appealing from a practical and fundamental viewpoint, for example for understanding geochemical events, or when using apatite precipitation for the elimination of metal cations from industrial wastewaters, or else for conferring magnetic properties to apatite systems in medicine. Based on multiple physico-chemical correlations, the present contribution extends the additive predictive model ThermAP to Ni-, Co-, Mn(II)- and Fe(II)-doped apatites. It provides for the first time estimations of enthalpies, Gibbs free energies of formation and entropies, unveiling the general stability ranking Mn(II)-apatite > Fe(II)-apatite > Co-apatite ⩾ Ni-apatite. This additive approach also allows one to estimate these properties for any composition in view of enabling thermodynamic calculations for applicative or fundamental purposes.